The Narrative of the Urban Landscape in the Frescoed Galleries of the Vatican Museums and Palazzo Doria Spinola (diségno, 2023)
“He who has experienced flight will walk looking at the sky because there he has been and where he wants to return”, so began the genius Leonardo about the studies he was making on flying machines. Not only Da Vinci, but the man in general, has always had a propensity for what he could not reach, an urge to create tools that would allow him to reach different points of view. Between Humanism and the Renaissance, the new cultural liveliness led man to undertake great geographical explorations, undertaking numerous studies to create detailed maps and charts.The wealthiest families and prominent personalities, in general, began to take an increasing interest in cartography, asking astronomers and cartographers to make maps for their homes that initially only contained descriptions of the ancient world, to be progressively updated with newly discovered areas. The fashion became so widespread that aristocratic and clerical buildings began to be decorated in paintings or frescoes; the pictorial maps in the Gallery of the Vatican Museums and the Gallery of Palazzo Doria Spinola in Genoa are famous examples.Therefore, the research aims to analyse the similarities and differences between these two cartographic representations in bird’s eye perspective views of the Ligurian capital.
Keywords: Cartography; Palazzo Doria Spinola; Vatican map gallery; urban landscapes; bird’s eye perspective